DISEÑO DE UN HUMEDAL CONSTRUIDO PARA EL TRATAMIENTO DEL AGUA DE PRODUCCIÓN DE UN CAMPO DE PETRÓLEO COLOMBIANO - Aracelly Caseles O.; Edwin Ricardo Zamora C.; Sergio Eduardo Díaz C. (Revista Fuentes El Reventón Energético, 2013)
The development of this paper permits to find and set a new and alternative solution to the big problem that Colombian petroleum fields are facing: Management and Disposal of produced water. Due to the conventional treatment facilities, petroleum companies are spending great amounts of money to treat and dispose petroleum wastewaters. The present project describes a full-scale constructed wetland design proposed as a secondary treatment for a Colombian field produced water.